THE IMPACT OF TOURISM ON DEVELOPMENT - Begamova Nasiba Kholmurzayevna (Western European Studies, 2025)
This article discusses the reforms being carried out in the field of tourism development, one of the fastest growing sectors of the country in today's development environment
Keywords: cultural heritage; ancient sites; green nature